2018
DOI: 10.1002/adfm.201802793
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Lateral Flow Cytochrome P450 Assay on a Novel Printed Functionalized Calcium Carbonate‐Based Platform for Rapid Screening of Human Xenobiotic Metabolism

Abstract: Cytochrome P450 (CYP) is a superfamily of enzymes in charge of elimination of the majority of clinically used drugs and other xenobiotics.This study focuses on the development of a rapid microfluidic lateral flow assay to study human phase I metabolism reactions mediated by CYP2A6 isoenzyme, the major detoxification route for many known carcinogens and drugs, with coumarin 7-hydroxylation, as the prototype model reaction. Assay fabrication utilizes custom-designed porous functionalized calcium carbonate (FCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…The global production and use of biofuels has increased dramatically in recent years, with about 85 % of this being bioethanol [31]. By 2030 the global population is expected to increase by 1.3 billion inhabitants, with rising middle class without any proper mindset of susta-inable consumption of goods and transport, which will create additional stress from pollution, inefficient land use and food production [12,29,32]. Bioethanol is the most common and one of the most ecologically friendly liquid biofuels, suitable for augmenting petroleum, that can be produced from a variety of cheap raw materials [8,20].…”
Section: Biofuels For Sustainable Reduction Of Greenhouse Gases -Currmentioning
confidence: 99%
See 1 more Smart Citation
“…The global production and use of biofuels has increased dramatically in recent years, with about 85 % of this being bioethanol [31]. By 2030 the global population is expected to increase by 1.3 billion inhabitants, with rising middle class without any proper mindset of susta-inable consumption of goods and transport, which will create additional stress from pollution, inefficient land use and food production [12,29,32]. Bioethanol is the most common and one of the most ecologically friendly liquid biofuels, suitable for augmenting petroleum, that can be produced from a variety of cheap raw materials [8,20].…”
Section: Biofuels For Sustainable Reduction Of Greenhouse Gases -Currmentioning
confidence: 99%
“…[7, [22]. In a recent publication, in which EU bioeconomy documents were analysed in order to understand the direction of development in forestry policies it was shown that by 2030 the global population is expected to increase by 1.3 billion inhabitants on top of the 7.6 billion currently [32].…”
Section: Modelling Sustainable Development (Sd) -The Regulatory Envirmentioning
confidence: 99%
“…A variety of capillary-based immobilized enzyme reactors (IMERs) have been implemented in the past, including covalent and non-covalent binding to a solid support material and entrapment inside a crosslinked polymer network [ 10 ]. Even lateral flow CYP assays [ 11 ] and nanoliter-scale microarrays with CYPs encapsulated in as many as 1134 parallel gel compartments patterned on a functionalized glass slide [ 8 ] have been reported. Implementation of microfluidic actuation and integration of other sample preparation and separation units with the IMER technology [ 12 ] would facilitate adaptation of even more mature lab(oratory)-on-a-chip technology concepts to drug metabolism research.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid structures comprising nanoscale cellulosic materials and inorganic minerals are an important material combination for diversity of applications varying from, for example, biomedical devices to renewable packaging materials and fire-retardant nanocomposites [ 1 , 2 , 3 , 4 , 5 , 6 ]. Furthermore, the bionanomaterial architectures with high porosity and large surface area combined with renewable and sustainable material attributes have gained increasing interest to be used, amongst other things, as high efficiency air filters and as substrates for biocatalytic conversion [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%